ETIKA PROFESI SEBAGAI PEMODERASI KEMAMPUAN DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT - J, Yulianti; Husaini, Husaini; Aisyah, Siti (JURNAL FAIRNESS, 2017)
The purposes of this research are to prove the influence of ability on the audit quality Bengkulu Province Inspectorate Auditors; to prove the influence of the auditors independency on the audit quality Bengkulu Province Inspectorate Auditors; to prove the moderating influence of the profession ethic on the correlation of ability on the audit quality on Inspectorate Auditors in Bengkulu Province and to prove the moderating influence of the profession ethic on the correlation of auditors independency on the audit quality Bengkulu Province Inspectorate Auditors.The data used in this research is the primary data which was gained by spreading the questionnaires to 101 respondents of Bengkulu Province Inspectorate Auditors. This research used multiple linear regression and moderated regression analysis.The research result are the ability have influences toward the audit quality on Inspectorate Auditors in Bengkulu Province; auditors independency have influences toward the audit quality on Inspectorate Auditors in Bengkulu Province; the profession ethics have moderating effect on correlation between ability and the audit quality on Inspectorate Auditors in Bengkulu Province; and the profession ethics have not moderating effect on the correlation between independency with the audit quality on Inspectorate Auditors in Bengkulu Province.